2017
DOI: 10.1111/jocn.13646
|View full text |Cite
|
Sign up to set email alerts
|

Vital signs as predictors for aggression in hospital patients (VAPA)

Abstract: Strategies are needed to improve physiological assessment of patients with behavioural disturbance while ensuring staff safety. There are patient and physiological factors associated with increased risk of Code Grey that may be used to prevent behavioural escalation to the point of an emergency response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Successful de-escalation by clinical staff might have avoided security intervention and is increasingly being taught among health professionals. 26 The findings of this report are limited by reliance on the accuracy of medical documentation and the assumption that missing data was missing at random. A similar effect might be attributed to including patients, potentially on the basis of staff suspicion, with undiagnosed psychiatric conditions as well as undetected drug or alcohol exposure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Successful de-escalation by clinical staff might have avoided security intervention and is increasingly being taught among health professionals. 26 The findings of this report are limited by reliance on the accuracy of medical documentation and the assumption that missing data was missing at random. A similar effect might be attributed to including patients, potentially on the basis of staff suspicion, with undiagnosed psychiatric conditions as well as undetected drug or alcohol exposure.…”
Section: Discussionmentioning
confidence: 97%
“…Despite this novel strategy to identify violent patients in the ED, there is still potential for these results to be an underestimate of true WPV incidence secondary to nurse and physician under‐reporting of violent events. Successful de‐escalation by clinical staff might have avoided security intervention and is increasingly being taught among health professionals …”
Section: Discussionmentioning
confidence: 99%
“…61.96% of respondents believe that the most frequent cause of aggressive behaviour is the patient's illness itself. The disease itself, as a cause of aggressive patient behaviour, has been reported in several studies of a similar nature (Considine et al, 2019;Edward et al, 2014;Šupínová, 2013). Fear and pain are closely related to the problem of the disease itself; 74.48% of respondents think that fear can cause aggressive behaviour in patients.…”
mentioning
confidence: 69%
“…Paying extra attention to RR and SBP is crucial as they serve as accurate indicators of immediate deterioration. Abnormal respiratory rate has been shown to frequently occur in patients that require immediate critical care management [20,22,24,32]. For instance, an increased respiratory rate frequently precedes adverse events such as cardiac arrest [22].…”
Section: Discussionmentioning
confidence: 99%
“…Using clinician interviews and observations, the authors found that EWS score is an effective communication mechanism for referring deteriorating patients to their doctors. In another study on predictors of critical care admissions from ED, Considine et al [22] conducted a retrospective case control study on ED adult patient cases admitted to the ICU or coronary care unit (CCU) and control cases admitted to the medical/surgical ward. Findings showed that deterioration in physiological indicators such as respiratory rate, temperature and heart rate tend to increase the risk of a critical care admission.…”
Section: Research Backgroundmentioning
confidence: 99%